The Uganda Tar Paper: A Ship’s Newspaper and Its Community - Butler, Malcolm A.P. (The Northern Mariner / Le marin du nord)

(untitled) (Canadian Nautical Research Society and North American Society for Oceanic History, 2025)
While HMCS Uganda’s operational records have been examined along with the impact of the volunteers-only policy for the Pacific Theatre implemented by the Canadian Government in April 1945, historians have largely overlooked HMCS Uganda’s shipboard newspaper called The Uganda Tar Paper. Recognising the importance of a newspaper to its community and that HMCS Uganda was the sole Canadian warship in combat operations in the Pacific Theatre, this oversight has impacted our understanding of the importance of the newspaper aboard ship and the experiences of the ship’s company. In response, this article offers an examination of the newspaper and its importance to the sense of community aboard while also contributing to the historiography of HMCS Uganda. Furthermore, this article examines the possible use of the newspaper by the senior leadership aboard to influence the results of the Pacific volunteer vote held aboard HMCS Uganda in June 1945.